Cluster approach to analysis of publication titles. Issue 1 (January 2021) - Bogomolova, Arina; Ryazanova, Maria; Balk, Igor
Abstract: Text analysis is a promising field of study with many unsolved problems. First of all, most methods are labor and time consuming. We want to pay special attention to patents. The most important thing in analyzing patents as a reflection of a company's research activities is not to be late. Technology is emerging very quickly. So speed of response to changes in the world of scientific research is very important now. Therefore, we propose an alternative method of patent analysis based on clustering. Its main advantage is that it does not require different train/test datasets and it could be applied immediately. In this article, we compare different clustering algorithms, because the quality of the conclusions depends on it.